Building a Smart Interactive Kiosk for Tourist Assistance - Amessafi, Hanane; Jourani, Reda; Echchelh, Adil; Yakhlef, Houssain Oulad (Transactions on Engineering and Computing Sciences, 2017)
The tourism sector in morocco is increasing rapidly, is well developed, with a strong tourist industry focused on the country’s coast, culture, and history. Morocco is the most politically stable countrie in North Africa, which has allowed tourism to develop. There are some tourist attractions spread over a wide geographical area, which are only visited by a few people at speciﬁc times of the year. Additionally, having human tourist guides everywhere and speaking different languages is unfeasible. This work deals with the build of a smart interactive kiosk for tourist assistance. In order to do this, it is necessary to start with an Automatic Language Recognition to recognize the language used by the tourist, then extracting keywords from what the tourist said by using Automatic Speech Recognition techniques among others, and finally the system analyses and ansers to the tourist query by suggesting a set of related informations.